Management Model of School Dental Health Effort (SDHE) of Website-Based for Improving Quality of Information System at Elementary School - Galuh Ayuning Suryo; Supriyana Supriyana; Rasipin Rasipin; Lanny Sunarjo; Diyah Fatmasari (Alta Dharma Publisher, 2021)
Dental and oral health services for elementary school students aged 6 to 12 years have not been optimal. This shows that the implementation of SDHE has not succeeded. Monitoring and evaluation of the performance of SDHE are complex because the reporting system of SDHE all this time is conducted manually at the end of the year using a form combined with the report of the health center. The website-based SDHE management model is an information system that can be used to report the activities of SDHE directly and monitor and evaluate the activities of SDHE to fit the targets that have been set. The study aimed to develop the SDHE management model's innovations with relevant/appropriate information systems to increase the effectiveness and efficiency in the implementation of SDHE in elementary school students. Methods: Research and Development (R&D) and model trials using the technique of pre-experimental. The respondents amounted to 48 populations which consist of 24 dental therapists and 24 teachers, to assess the quality of SDHE management and the quality of information systems in the implementation of SDHE management. The result of the design of the model was tested for validation by an expert. The data were tested using paired difference test, proportion test, and linear regression test. Result: Validation by expert result the average value of 92, the category is very feasible, and with a p-value of 0,014. After the intervention, the E-SDHE information system's quality also improved compared to before (p = 0.001). Respondent's assessment stated that the quality of the E-SDHE information system in the excellent category. The SDHE management model of elementary schools based on the website provides a significant increase in SDHE management quality and the quality of information systems in the excellent category. The SDHE of website-based in this study can be used to evaluate elementary school health managemen